Peran Literasi Keuangan dan Literasi Keuangan Digital terhadap Inklusi Keuangan: Studi pada Nasabah Bank Syariah di Kota Tangerang dengan Media Sosial sebagai Moderator - Salsabila, Tiara Shalihah; Amri, Andi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
This study aims to understand the extent of the influence of understanding of Financial Literacy and Digital Financial Literacy on the Customer's decision to use financial services, especially considering the role of Social Media as a medium of information delivery and interaction. Using quantitative method, this study examines the effect of one variable on another, where there are three types of variables involved, namely independent variables in the form of financial literacy and digital financial literacy, dependent variables in the form of financial inclusion, and moderator variables in the form of social media. Sharia Bank customers in Tangerang City were the object of this study, with data collected through a Likert scale questionnaire. The results of this study indicate that the variables used are able to explain the intention of Islamic Bank Customers towards Financial Inclusion with a good level of accuracy. The direct effect of digital financial literacy and social media variables on financial inclusion is significant, while moderation by social media is only significant in the relationship between financial literacy and financial inclusion.